2022
DOI: 10.3390/ijms23147673
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine Inhibits Colorectal Cancer Cell Migration through Mirna-Mediated Targeting of Notch Signaling Pathway

Abstract: Metastasis is a leading cause of mortality and poor prognosis in colorectal cancer (CRC). Thus, the identification of new compounds targeting cell migration represents a major clinical challenge. Recent findings evidenced a central role for dysregulated Notch in CRC and a correlation between Notch overexpression and tumor metastasis. MicroRNAs (miRNAs) have been reported to cross-talk with Notch for its regulation. Therefore, restoring underexpressed miRNAs targeting Notch could represent an encouraging therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
2
1
Order By: Relevance
“… 29 SAM has also upregulated miRNAs to suppress CRC cell migration. 30 These findings differ from those of our study. In light of these disparities, we suggest that the dosage of SAM administered to the colon cancer cells may have contributed to these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“… 29 SAM has also upregulated miRNAs to suppress CRC cell migration. 30 These findings differ from those of our study. In light of these disparities, we suggest that the dosage of SAM administered to the colon cancer cells may have contributed to these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that SAM significantly reduced vimentin levels and promoted the transformation from N-cadherin to E-cadherin expression in HCT-116 and Caco-2 cells, as demonstrated by comparing the strength of corresponding protein bands in SAM treated and untreated cells. This highlights the ability of SAM to slow CRC cell migration by inhibiting the transition from epithelial to mesenchymal states[ 33 ]. SAM inhibits CRC cell growth by reversing the hypomethylation of c-Myc and H-ras promoters, thereby inhibiting the expression of these oncogenes[ 34 ].…”
Section: Methionine and Colorectal Cancermentioning
confidence: 99%
“…Increasing evidence has also demonstrated that the epigenetic regulation of oncogenic or tumor-suppressor microRNAs represents one of the main mechanisms underlying the anticancer activity of AdoMet [30,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%